Biomaterials for Tissue Engineering. - Razavi, Mehdi (Sharjah : Bentham Science Publishers, 2017)
This volume reviews the published knowledge about bioactive composites, protein scaffolds and hydrogels. Chapters also detail the production parameters and clarify the evaluation protocol for analysis or testing and scaffolding biomaterials. The volume concludes with a summary of applications of porous scaffold in medicine. Each chapter links basic scientific and engineering concepts to practical applications for the benefit of the reader. The text offers a wealth of information that will be of use to all students, bioengineers, materials scientists, chemists and clinicians concerned with the properties, performance, and use of tissue engineering scaffolds -- from research engineers faced with designing the biomaterials and techniques to physicians and surgeons charged with shepherding the use of the scaffolds into the applied clinical settings.
Functionalization and Surface ModificationTailoring the Properties of Synthetic Polymer, Importance of Polymer Physics -- Blending and Thermodynamic Aspects -- Soft Nanoparticles -- Biomimetic Strategies -- CONFLICT OF INTEREST -- ACKNOWLEDGEMENTS -- REFERENCES -- Polymer-Based Biocomposites -- Yasemin Budama-Kilinc*, Rabia Cakir-Koc, Ilke Kurt, Kubra Gozutok, Busra Ozkan, Burcu Ozkan and Ibrahim Isildak -- INTRODUCTION -- IMPORTANCE OF SYNTHETIC POLYMERIC BIOCOMPOSITES (SPBC) -- SPECIFIC MECHANICAL AND BIOLOGICAL PROPERTIES OF SPBC
Online resource; title from PDF title page (EBSCO, viewed January 9, 2018).
""Poly(dimethyl siloxane)/Poly(N-isopropylacrylamide)(PDMS/PNIPAAM)""
eBooks on EBSCOhost
Keywords: Biomedical materials; Tissue engineering; Tissue Engineering; Biomatériaux.; Génie tissulaire; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Biotechnology; SCIENCE; Biomedical materials; Tissue engineering